THE DISTRIBUTION OF TOXIC BHENTIK DINOFLAGELLATE Gambierdiscus sp. Prorocentrum sp AND Ostreopsis sp ON Sargassum sp IN THE COASTAL OF SUNGAI NIPAH, PESISIR SELATAN REGENCY, WEST SUMATRA PROVINCE - Winda Eboni; Thamrin '; Mubarak ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Ciguatera Fish Poisoning (CFP), can be caused by ciguatoxin from groups such as the bhentic dinoflagellate of Gambierdiscus sp., Ostreopsis sp., and Prorocentrum sp.,the bhentic dinoflagellates potentially toxic. In addition as bhentic organisms these three bhenthic dinoflagellates also found associated with brown algae, red algae, coral fragments and also attached on seaweed . Research on the distribution of the toxic dinoflagellate benthic Sargassum sp in the coastal waters of Sungai Nipah Beach of Pesisir Selatan Regency of West Sumatra Province was conducted in April 2014 with the to analyze the abundance and distribution of benthic dinoflagellate Gambierdiscus sp. Ostreopsis sp Prorocentrum sp. The study was conducted by taking a substrate attachment of benthic dinoflagellates from the seaweed, and then put them in a plastic screen of sea water. For the releasing of the benthic dinoflagellate the process agitation and filtration were used with filter of 250μm and 20μm. The samples observed by using microscope and Sedgwick Rafter Cell. The highest abundance was found at stations with high density (45.85 cells/gram). The research showed that the abundance and distribution of toxic dinoflagellate types of seaweed in coastal waters in Sungai Nipah was more influenced by local currents.Keywords : Dinoflagellata, Distribution, Sargassum sp, West Sumatera